Control of dynamic failure of brittle rock using expansive mortar - Wang, Lu (2022)
Control of rock failure under stress wave loading is challenging but important to mitigate the negative impacts of underground excavation on the environment (e.g., rock overbreak and ground vibration). This study reports that dynamically amplified expansion pressure from expansive mortar is an effective and efficient solution to promote the dynamic failure of brittle rock. Our experimental and numerical results reveal that the expansion pressure amplified by stress wave loading facilitates the dynamic failure surrounding the expansive mortar, accompanied by the generation of tangential and radial cracks and the attenuation of stress wave. Our data also show that the dynamically amplified expansion pressure is larger than the radial inertia stress and dominates crack generation in the unconfined rock, but the pressurization capacity of expansive mortar should be improved for the rock fracturing application in confined rock. The application of expansive mortar fundamentally modifies the brittleness of surrounding rock under stress wave loading, resulting in changes in failure mode. However, the application of expansive mortar to control rock dynamic failure should be further investigated in field studies.